The private sector as a catalyst for health equity and a vibrant economy : proceedings of a workshop - Anderson, Karen M.; Olson, Steve, 1956- (National Academies Press, 2016)
A critical component of the nation's economic vitality is ensuring that all Americans can contribute and prosper. Such contributions presuppose an intentional focus on achieving the highest levels of health possible, which requires that conditions in communities, schools workplaces, and other settings promote health and address the social determinants of health for all community members. Many organizations, in both the private and public sectors, have been establishing partnerships to further healthy workplaces and health equity in general. Many are taking the lead in producing economic growth that is inclusive and responsive to the nation's diverse needs and populations. Increasingly, private-public partnerships are emerging as ways of doing business. Additionally, a variety of new developments in health, health care, and community benefits obligations that are part of the Affordable Care Act have contributed to this interest in economic growth and health and in the creation of new partnerships. To examine past successes and future opportunities, the National Academies of Sciences, Engineering, and Medicine held a workshop in November 2015. The workshop focused on the potential of the private sector to produce a triple bottom line: economic opportunity (including workforce development) and growth, healthy work and community environments, and improved employee health. At the same time, participants looked beyond the private sector to public-private partnerships and to public-sector actions that combine opportunities for economic growth and good health for all. This publication summarizes the presentations and discussions from the workshop.